2017
DOI: 10.1111/jmwh.12580
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Hydrotherapy Protocol to Improve Postpartum Pain Management

Abstract: This project demonstrated successful implementation of a hydrotherapy protocol as an alternative or adjunct to medication for early postpartum pain management that significantly reduced pain and improved the birth experience for those who used it. It offers a nonpharmacologic alternative where there have traditionally been limited options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
0
12
1
1
Order By: Relevance
“…Relieving pain during childbirth represents an important challenge for both health care professionals and pregnant women (16)(17)(18)(19)(20). Pain relief strategies include non-pharmacologic and pharmacologic approaches (20)(21)(22)(23)(24)(25). In obstetrics, pharmacologic methods such as epidural anesthesia have proven to be efficient in reducing pain during labor and are now routinely used, and even expected, to manage pain (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relieving pain during childbirth represents an important challenge for both health care professionals and pregnant women (16)(17)(18)(19)(20). Pain relief strategies include non-pharmacologic and pharmacologic approaches (20)(21)(22)(23)(24)(25). In obstetrics, pharmacologic methods such as epidural anesthesia have proven to be efficient in reducing pain during labor and are now routinely used, and even expected, to manage pain (18).…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacologic approaches to relieve pain during labor, when used as a part of hospital pain relief strategies, provide significant benefits to women and their infants without causing additional harm. Non-pharmacological methods of labor analgesia in- clude doula support during labor and delivery, music therapy, postural changes, water immersion and birth, and acupuncture (20)(21)(22)(23)(24). A Cochrane systematic review of immersion in water in labor and birth found that immersion in water significantly reduced the duration of the first stage of labor and reduced the use of epidural anesthesia, but did not significantly reduce intrapartum C-section in the included RCTs (25).…”
Section: Discussionmentioning
confidence: 99%
“…The critical analysis of the results (Table 2) showed that LEs ranged from 1 to 5, with 8 (29.6%) three meta-analyzes 18,25,32 , five systematic reviews of RCTs (SRRCT) 24,27,28,33,35 and 6 (22.2%) randomized clinical trials (RCT) 14,20,21,30,34,39 were found in LE 1 and 2 respectively; non-randomized controlled trials (NRCT) [15][16][17]22,23,26,29,31,[37][38]40 11 (40.7%) (LE 3); a Cohort 19 (3,7%) in LE 4; in LE 5 only one (3.7%) qualitative and quantitative descriptive study was identified 36 and none in the LE 6 and 7. Therefore, the studies focused on the hierarchical levels of evidence 1 to 3 12,13 considered high and moderate and when related to the quality of strong and sufficient evidence levels 13 , respectively, demonstrating that the PICS studied appear to be effective in pain control.…”
Section: A26mentioning
confidence: 99%
“…The most common method used to relieve after-pains is oral analgesics such as acetaminophen and ibuprofen (13). However, some analgesics (e.g., mefenamic acid and ibuprofen) sometimes cause side effects such as nausea, vomiting, diarrhea, abdominal pain, bleeding, gastrointestinal obstruction or perforation, dizziness, drowsiness, seizures, acute renal failure, and interstitial nephritis (14,15).…”
Section: Introductionmentioning
confidence: 99%